Formation of methane-derived carbonates during the last glacial period on the northern slope of the South China Sea. (December 2018) - Yang, Kehong; Chu, Fengyou; Zhu, Zhimin; Dong, Yanhui; Yu, Xiaoguo; Zhang, Weiyan; Ma, Weilin
Graphical abstract: Highlights: Carbonates with different morphologies were studied for tracing microenvironments and fluid seepage. New U-Th dating results reveal the growth order of chimney carbonates. REE results indicate that the redox environments are various. Abstract: Methane-derived carbonates with blocky and chimney morphologies were collected on the northern slope of the South China Sea. The studies of petrography, geochemistry and chronology show that the blocky carbonate has a microcrystalline structure with numerous of biogenic tests, whereas the carbonate chimney has a cryptocrystalline structure with scarce biogenic tests. Aragonite can be detected in the carbonate chimney, which indicates that it formed at the shallow sediments or on the seafloor. The δ 13 C and δ 18 O values of the blocky carbonate range from −46.8‰ to −28.8‰ VPDB and 2.2‰ to 3.5‰ VPDB, respectively. The δ 13 C and δ 18 O values of the carbonate chimney range from −45.0‰ to −22.9‰ VPDB and −2.8‰ to 3.1‰ VPDB, respectively. The carbon isotopic values indicate that these carbonates are related to the anaerobic oxidation of methane (AOM). The oxygen isotopic values show that the gas hydrate dissociation contributed the 18 O-enrich fluid to a certain degree during the authigenic carbonate formation. According to the rare earth element results, the carbonate chimney precipitated in stable anoxic conditions. Because of the La-enriched influence, the formation environment of the blocky carbonate is ambiguous. The U/Th chronology results indicate that these authigenic carbonates precipitated during the last glacial period (primarily Marine Isotopic Stage 3) of low sea level stand.